Efficacy and safety of active silicone oil removal through a 23-gauge transconjunctival cannula using an external vacuum pump - Hyun Ju Oh; Woohyok Chang; Min Sagong (International Journal of Ophthalmology, 2015)
AIM: To evaluate the efficacy and safety of active removal of silicone oil with low and high viscosity through a 23-gauge transconjunctival cannula using an external vacuum pump. METHODS: This study was conducted as a prospective, interventional case series. A total of 22 eyes of 21 patients [1000 centistokes (cSt): 17 eyes, 5700 cSt: 5 eyes] were included in this study. All patients underwent active silicone oil removal via the entire lumen of a 23-gauge microcannula with suction pressure of a 650-700 mm Hg vacuum using an external vacuum pump. A tubing adaptor from the Total Plus Pak® (Alcon, Fort Worth, USA) was used to join the microcannula and silicone vacuum tube connected to an external vacuum pump. Main outcome measures were mean removal time, changes of intraocular pressure (IOP) and visual acuity, and intraoperative and postoperative complications. RESULTS: Mean removal time (min) was 1.49±0.43 for 1000 cSt and 7.12±1.27 for 5700 cSt. The IOP was 18.57±7.48 mm Hg at baseline, 11.68±4.55 mm Hg at day 1 postoperatively (P<0.001), and 15.95±4.92, 16.82±3.81, 17.41±3.50, and 17.09±3.01 mm Hg after one week, one month, three months, and six months, respectively. All patients showed improved or stabilized visual acuity. There was no occurrence of intraoperative or postoperative complications during the follow up period. CONCLUSION: This technique for active removal of silicone oil through a 23-gauge cannula using an external vacuum pump is fast, effective, and safe as well as economical for silicone oil with both low and high viscosity in all eyes with pseudophakia, aphakia, or phakia.